Clinical course of acute chemical lung injury caused by 3-chloropentafluoropene. (5th December 2013) - Morita, Satomu; Takimoto, Takayuki; Kawahara, Kunimitsu; Nishi, Katsuji
Abstract : Perfluoroallyl chloride (PFAC), a fluorine-containing compound, has very severe toxicity, but this toxicity is not well characterised. We report a fatal case of acute chemical lung injury caused by the inhalation of PFAC. A 39-year-old man, working at a chemical factory, inhaled PFAC gas and died 16 days later of acute lung injury with severe pneumothorax. We present his clinical course together with thoracic CT findings, autopsy and analysis of PFAC in blood and urine samples with gas chromatograph–mass spectrometry. Previously, a fatal case of PFAC was reported in 1981 but PFAC was not identified in any of the patient's samples. In our patient, we identified PFAC in both blood and urine samples. Our toxicological analysis may be used as a reference to detect PFAC toxicity in the future. Our study should be helpful for diagnosing lung injury induced by a highly toxic gas, such as PFAC.